Neuronal Migration and Lamination in the Vertebrate Retina - Amini, Rana; Rocha-Martins, Mauricio; Norden, Caren (Frontiers in Neuroscience, 2018)
In the retina, like in most other brain regions, developing neurons are arranged into distinct layers giving the mature tissue its stratified appearance. Neuronal layering defects lead to impaired retinal function and thus this process needs to be highly controlled and orchestrated. To achieve successful neuronal layering and lamination in the retina and beyond, three main developmental steps need to be executed: Firstly, the correct type of neuron has to be generated at a precise developmental time. Secondly, as most retinal neurons are born away from the position at which they later function, newborn neurons have to move to their final layer within the developing tissue. Thirdly, these neurons need to connect to the correct synaptic partners. We will discuss neuronal migration and lamination in the vertebrate retina and summarize our knowledge on these, in our opinion, currently understudied aspects of retinal development. We give an overview of how lamination emerges and discuss the different modes of neuronal translocation that occur during retinogenesis and what we know about the cell biological machineries driving them. In addition, synaptic connectivity and retinal mosaics and their importance for correct retinal function will be examined. We close by pointing out open questions and future directions in this exciting field.